Patient and family experience of physical rehabilitation on the intensive care unit: a qualitative exploration. (December 2020) - van Willigen, Zoe; Ostler, Chantel; Thackray, Debbie; Cusack, Rebecca
Abstract: Objectives: To explore the experience of physical rehabilitation in the intensive care unit (ICU), from the perspective of patients and relatives. Design: Exploratory, qualitative study. Participants: Five former ICU patients and five family members of former ICU patients recruited from ICU support groups across the UK. Interventions: Semi-structured interviews. Main outcome measures: Participants' experiences of physical rehabilitation in the ICU. Data were analysed using an iterative thematic approach. Results: Four main themes were identified: Trust and Rapport, Necessity (of treatment), Psychological Benefit, and Goal Setting: Whose goal is it anyway? Despite a lack of enjoyment, patients tend to comply with physical rehabilitation, due in part to a positive patient–therapist relationship. There was agreement across participants that physical rehabilitation should be started as soon as possible after admission to ICU and exhaustion was highlighted as the biggest challenge to participation. In addition to aiding physical recovery, physical rehabilitation in the ICU may also provide psychological support for both patients and relatives. Finally, participants described a desire for therapists to direct goal setting in the early stages of recovery as they felt unable to engage in the process due to other priorities. Conclusions: The experience of physical rehabilitation on ICU may be influenced by key aspects of person-centred care. This study suggests that patients and relatives are keen for physical rehabilitation to start as soon as possible, which is a crucial new finding to support the practice of early rehabilitation in the ICU.